Memanfaatkan teknologi guna mPembelajaran IPS yang interaktif di SMP Islam Bani Hasyim Singosari - Kurniawati, Sinta (Maliki Interdisciplinary Journal, 2024)
English abstract. The maximum length of the abstract is 200 words. There are no strict requirements on Social Sciences (IPS) learning has an important role in forming an intelligent, critical and responsible young generation. However, in many cases social studies learning still seems boring and uninteresting for students. This is caused by several factors, such as monotonous learning methods, lack of interactive learning media, and limited technological infrastructure in schools. Interactive social studies learning is a solution to overcome this problem. This article uses a qualitative approach with a case study method. The data collection techniques used were interview and observation techniques. Several types of technology that can be used to create interactive social studies learning at Bani Hasyim Islamic Middle School include interactive whiteboards, projectors, laptops, cellphones, educational games, social media, and editing applications. The use of this technology provides benefits in the form of increasing student motivation and interest in learning, increasing student interaction and participation, and helping students learn independently and actively. However, challenges such as inadequate technological infrastructure and unequal access need to be addressed with solutions such as internet-free learning and the formation of study groups. It is hoped that the application of technology in social studies learning can achieve the desired learning objectives at Bani Hasyim Singosari Islamic Middle School.